2012
DOI: 10.1016/j.applanim.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in stereotypic behaviour predict individual differences in the nature and degree of enrichment use in caged American mink

Abstract: a b s t r a c tEnvironmental enrichment (EE) reduces stereotypic behaviour (SB), but typically only partially. Using American mink (n = 17) as models, we tested the hypotheses that the effectiveness of EE reflects the degree to which subjects utilise it, and also the SB's degree of 'establishment' (its frequency and within-bout predictability). In Non-Enriched cages, our subjects performed Carnivora-typical Locomotor SBs; some also stereotypically scrabbled against the cage walls. Each mink was then enriched: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Hansen et al, 2007;Mason et al, 2001) as motivating and stress-reducing for mink. Previous studies from our laboratory confirmed that these cages benefit mink: subjects would push heavily weighted doors to access them (Dallaire et al, 2012), and they reduced stereotypic behaviour, faecal glucocorticoid metabolites, and several other signs of stress in animals raised in them (Díez-León and Mason, 2010;Campbell et al, 2013). Our first set of hypotheses was that non-enriched cages would: 1a) reduce time spent sleeping rather than lying awake; 1b) increase time spent inactive in the nest-box, and decrease inactive time in exposed areas of the cage; and 1c) influence the postures shown while inactive.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Hansen et al, 2007;Mason et al, 2001) as motivating and stress-reducing for mink. Previous studies from our laboratory confirmed that these cages benefit mink: subjects would push heavily weighted doors to access them (Dallaire et al, 2012), and they reduced stereotypic behaviour, faecal glucocorticoid metabolites, and several other signs of stress in animals raised in them (Díez-León and Mason, 2010;Campbell et al, 2013). Our first set of hypotheses was that non-enriched cages would: 1a) reduce time spent sleeping rather than lying awake; 1b) increase time spent inactive in the nest-box, and decrease inactive time in exposed areas of the cage; and 1c) influence the postures shown while inactive.…”
Section: Introductionmentioning
confidence: 69%
“…NE cages were 75 (L) x 60 (W) x 45 (H) cm, with a nest-box on the front. E cages consisted of an identical home cage, plus access to a second cage 120 cm wide via an overhead "tunnel" built of wire mesh (see diagram in Dallaire et al 2012). This second cage included a trough of running water to allow wading and head-dipping, a plastic "hammock", and many manipulable objects, new ones added monthly.…”
Section: Housing Treatmentsmentioning
confidence: 99%
“…This was double the size of the home cage, and contained an extra nestbox, a swing, circulating water in which to wade, and several manipulable objects, some familiar, some new each month (Díez‐León et al, ; Díez‐León, ). These enrichments were known to be highly preferred by mink (Dallaire et al, ), and the whole enriched environment was known to be effective at reducing stereotypic behavior, physiological stress, and perseveration (Mason et al, ; Hansen et al, ; Campbell et al, ; Díez‐León et al, ); our females were born and raised in these environments. E females were successfully encouraged to whelp in the home cage's nest box by never providing nesting material in the enriched compartment's nest box.…”
Section: Introductionmentioning
confidence: 98%
“…Replacing enrichment items every week has similarities with housing rats in cages containing different enrichment items which has been shown to produce different responses and to vary in its effects on welfare (Abou-Ismail, 2011;Dallaire et al, 2012;Campbell et al, 2013;Sharp et al, 2014).…”
Section: Discussionmentioning
confidence: 99%